2019
DOI: 10.1002/hed.25962
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic association of presence of a somatic GNAQ mutation with port‐wine stain distribution in capillary malformation

Abstract: Background A somatic mutation of GNAQ (c.548G>A, p.Arg183Gln) plays a key role in capillary malformation development. The present study aimed to evaluate clinical manifestations of port‐win stain (PWS) associated with this genetic mutation. Methods Skin tissue was obtained from 70 patients with capillary malformation who had been treated with excision for lesions. Droplet digital polymerase chain reaction was used to quantify the abundance of cells with the GNAQ mutation. Results The GNAQ mutation was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…As noted above, PWB lesions can occur anywhere on the body but are particularly prevalent around the head and neck. Without treatment (or with treatment-resistant PWB), cutaneous lesions have the potential to progress with vascular hyperplasia, increasing prevalence of ectatic (dilated) vessels that cause the skin to darken in color (from pink or red to purple), and in some cases nodularity can develop ( Yin et al, 2017 ; Lee et al, 2019 ). Perivascular cell disorganization is also observed ( Couto et al, 2016 ).…”
Section: Port-wine Birthmarkmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, PWB lesions can occur anywhere on the body but are particularly prevalent around the head and neck. Without treatment (or with treatment-resistant PWB), cutaneous lesions have the potential to progress with vascular hyperplasia, increasing prevalence of ectatic (dilated) vessels that cause the skin to darken in color (from pink or red to purple), and in some cases nodularity can develop ( Yin et al, 2017 ; Lee et al, 2019 ). Perivascular cell disorganization is also observed ( Couto et al, 2016 ).…”
Section: Port-wine Birthmarkmentioning
confidence: 99%
“…Alternatively, xenotransplants can be used where mutant human EC in Matrigel extracellular matrix are subcutaneously injected into mice to study vessel formation, albeit outside the normal PWB/SWS environment. Most data to date identifying mutant GNAQ and possible molecular interactions leading to pathology have been developed using genome (DNA) sequencing and histology of patient tissue samples ( Shirley et al, 2013 ; Nakashima et al, 2014 ; Couto et al, 2016 ; Huang et al, 2017 ; Bichsel and Bischoff, 2019 ; Le Guin et al, 2019 ; Lee et al, 2019 ; Cong et al, 2020 ; Jordan et al, 2020 ). Additional in vivo and in vitro complex studies like those performed by Huang et al are needed to advance our understanding of PWB.…”
Section: Models Of Port-wine Birthmark/sturge-weber Syndromementioning
confidence: 99%
“…A study identified that GNAQ (R183Q) mutations were more common in individuals with PWSs involving all three facial regions (upper, middle, and lower) than in individuals with PWSs involving just one or two [ 43 ]. Additionally, the patients with PWSs involving extremities showed a lower rate of GNAQ (R183Q) mutations than those with PWSs affecting the head and neck.…”
Section: Pathogenesismentioning
confidence: 99%
“…The most simple CM would be a nevus simplex, commonly known as an “angel kiss” or “stork bite.” More extensive cutaneous CMs (also known as “naevus flammeus” or “port‐wine stains”) are seen in isolation or part of syndromes. CMs are associated with the GNAQ sporadic mutation and many are plagued with additional hypertrophy of involved segments of the soft tissue or skeleton 30,31 . Histologically, they are characterized by ectatic vessels within the superficial vascular plexus 32 .…”
Section: Capillary Malformationsmentioning
confidence: 99%